A black mica interlayer confined copper catalytic material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611210523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
AI Technical Summary
然而,目前对于云母类矿物在过一硫酸盐活化中的应用,多停留于将其作为一般性矿物载体或结构基底,尚未充分发挥黑云母本征结构二价铁的电子调控优势
本发明提供了一种黑云母层间限域铜催化材料,包括黑云母骨架,以及负载在所述黑云母骨架层间的铜物种,所述铜物种与黑云母骨架中本征结构Fe(II)发生电子耦合;所述铜物种包括Cu(I)和/或Cu(II);所述黑云母层间限域铜催化材料中铜含量为0.2~3wt.%,铁含量为4~9wt.%。
Smart Images

Figure CN122955486A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental remediation technology, specifically relating to a biotite interlayer confined copper catalytic material, its preparation method, and its application. Background Technology
[0002] With the increasing variety and concentration of recalcitrant organic pollutants in industrial wastewater, pharmaceutical wastewater, and polluted surface and groundwater, the development of efficient, stable, and low-cost environmental remediation materials and treatment technologies has become an important research direction in the field of environmental governance. Persulfate (PMS) advanced oxidation technology has received widespread attention in pollution control in recent years due to its advantages such as strong oxidation capacity, wide applicability, and good removal effect on various organic pollutants. The key to this technology lies in constructing catalytic materials that can efficiently activate PMS, thereby improving the generation efficiency of reactive oxygen species (ROS) and the removal effect of pollutants. Existing persulfate activation materials mainly include metal oxides, carbon-based materials, homogeneous transition metal ions, and their composite systems. Although these materials can achieve persulfate activation to a certain extent, they generally suffer from problems such as high preparation costs, limited utilization of active sites, significant risk of metal loss, insufficient structural stability, and poor adaptability to complex aquatic environments. Therefore, the development of novel mineral-based catalytic materials that are widely available, structurally stable, capable of efficient activation, and environmentally friendly has significant application value.
[0003] Natural layered silicate minerals, due to their unique layered structure, high structural stability, and excellent interfacial regulation potential, show promising application prospects in the field of environmental functional materials. Among them, mica minerals, with their regular layered framework and tunable interlayer structure, can serve as both loading or confining supports for active components and can be used to regulate interfacial reaction processes. Therefore, utilizing mica minerals to construct interfacial confined active materials has become an important direction in the development of natural mineral-based environmental catalytic materials in recent years. Among mica minerals, biotite not only possesses layered structural characteristics but is also rich in structural iron, especially containing a high proportion of structural divalent iron, giving it a potential advantage over ordinary inert mineral supports in interfacial electron transfer and redox reactions. On the other hand, copper-based active sites exhibit good redox activity and show promising application potential in peroxide and persulfate activation systems. If copper species can be stably introduced into the interlayer of biotite, and the synergistic effect between the intrinsic iron structure of biotite and the interlayer copper species can be utilized, it is hoped that a novel active material with both interlayer confinement effect and metal synergistic redox characteristics can be constructed, thereby improving the activation efficiency of persulfate and the removal capacity of organic pollutants. However, the current application of mica minerals in persulfate activation is mostly limited to using them as general mineral carriers or structural substrates, and the electronic regulation advantages of the intrinsic divalent iron structure of biotite have not been fully utilized. In particular, there is a lack of material design ideas that can utilize the layered structure of biotite to achieve interlayer confinement of copper species, and further utilize the Fe(II) structure to induce the formation of highly active low-valence species of interlayer copper and construct Fe-Cu synergistic active centers. In other words, the existing technology has not yet solved the following key problem: how to transform biotite from a simple mineral carrier into a reaction platform with both interlayer confinement function and intrinsic electron supply function, so as to achieve efficient activation of persulfate and removal of organic pollutants. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a biotite interlayer confined copper catalytic material, its preparation method, and its application. The biotite interlayer confined copper catalytic material provided by this invention can efficiently activate PMS and achieve a high removal rate of organic pollutants.
[0005] This invention provides a biotite interlayer confined copper catalytic material, comprising a biotite framework and copper species loaded between the layers of the biotite framework, wherein the copper species are electronically coupled to the intrinsic Fe(II) structure in the biotite framework. The copper species include Cu(I) and / or Cu(II); The biotite interlayer confined copper catalytic material contains 0.2-3 wt.% copper and 4-9 wt.% iron.
[0006] Preferably, the copper content in the biotite interlayer confined copper catalyst is 1.07~2.95 wt.%, and the iron content is 4.58~8.18 wt.%.
[0007] This invention also provides a method for preparing the biotite interlayer confined copper catalytic material described in the above technical solution, comprising the following steps: Biotite powder was purified using a buffer solution to obtain purified biotite powder; the pH value of the buffer solution was 4-6. The purified biotite powder and copper salt solution were mixed, and the pH of the system was adjusted to 1-5. The mixture was then subjected to ultrasonic treatment in an oxygen-deficient environment to separate the solid and liquid phases. The resulting solid was washed and dried sequentially to obtain the biotite interlayer confined copper catalytic material. Preferably, the copper salt in the copper salt solution includes one or more of copper nitrate, copper chloride, and copper sulfate; the concentration of the copper salt solution is 0.05~0.4 mol / L.
[0008] Preferably, the solvent of the copper salt solution includes water and an alcohol solvent, wherein the alcohol solvent includes one or more of ethanol, isopropanol and ethylene glycol, and the volume fraction of the alcohol solvent in the solvent is 5-40%.
[0009] Preferably, the pH of the system is adjusted to 3-4 after the purified biotite powder and copper salt solution are mixed.
[0010] Preferably, the frequency of the ultrasonic treatment is 20~60kHz and the ultrasonic power is 300~800W.
[0011] Preferably, the ultrasonic treatment time is 30~120 min.
[0012] The present invention also provides the application of the biotite interlayer confined copper catalyst material described in the above technical solution or the biotite interlayer confined copper catalyst material obtained by the above preparation method in the removal of organic pollutants.
[0013] Preferably, the application includes the following steps: mixing the biotite interlayer confined copper catalyst, the system to be treated containing organic pollutants, and persulfate, and reacting them under stirring and light-protected conditions.
[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a biotite interlayer confined copper catalytic material, comprising a biotite framework and copper species supported between the layers of the biotite framework, wherein the copper species are electronically coupled to the intrinsic Fe(II) structure in the biotite framework; the copper species include Cu(I) and / or Cu(II); the copper content in the biotite interlayer confined copper catalytic material is 0.2~3 wt.%, and the iron content is 4~9 wt.%.
[0015] The biotite interlayer confined copper catalytic material of this invention, through the synergistic coupling of intrinsic iron in the biotite structure with interlayer copper sites, can significantly improve the removal performance of organic pollutants. This material combines the enrichment effect of the interlayer confined microenvironment with the advantages of Fe / Cu synergistic redox, promoting the efficient generation and utilization of reactive oxygen species, achieving rapid degradation of various organic pollutants in a short reaction time, exhibiting excellent catalytic activity and good versatility.
[0016] This invention provides a method for preparing the biotite interlayer confined copper catalytic material described in the above technical solution, and further, it has the following advantages: (1) This invention constructs copper active centers with well-defined interlayer confinement characteristics. This invention utilizes ultrasonic cavitation, microjets, and water-alcohol wetting to promote the entry of copper species from the interlayer edges, defects, and microcrack channels of biotite into the interlayer. The resulting active sites are different from conventional surface-loaded metal sites, exhibiting higher structural order and interfacial stability, which is beneficial for improving the utilization efficiency of active components and reducing the risk of loss.
[0017] (2) This invention utilizes the intrinsic Fe(II) structure of biotite to induce the formation of active cuprous species from interlayer copper in an oxygen-deficient water-alcohol microenvironment. This invention avoids the use of exogenous reducing agents such as borohydrides, fully leveraging the electronic regulation effect of the divalent iron in biotite. During the ultrasound-assisted introduction of copper species into the interlayer, some interlayer copper is induced to transform from a divalent state to a lower valence state, forming cuprous species with higher reactivity. This process not only differs from the simple adsorption or loading of metal ions by ordinary mineral carriers but also endows the material with unique valence state regulation capabilities and electron transfer characteristics, providing a more favorable active site basis for subsequent persulfate activation.
[0018] (3) The preparation process is mild and the material system has good engineering application potential. The present invention uses natural biotite as the base material. The preparation process does not use a hydrothermal reactor, does not require borohydride reducing agent or exogenous iron salt loading step. The conditions are mild, the steps are simple and the cost is low. Moreover, the obtained material has good cycle stability and reusability, and is suitable for promotion to the field of organic pollution control and environmental remediation. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1The XRD patterns of the material and the control material in Example 1 of this invention are shown below. Figure 2 Infrared spectra of the material and control material in Example 1 of this invention; Figure 3 The fine XPS spectrum of Cu 2p material in Example 1 of this invention; Figure 4 The fine Fe 2p XPS spectra of the material and the original purified biotite in Example 1 of this invention; Figure 5 This is a kinetic curve of the degradation of 4-chlorophenol by activated PMS using the material from Example 1 of this invention and the control material. Figure 6 The graph shows the performance of the material prepared under different ultrasonic intercalation conditions in degrading 4-chlorophenol. Figure 7 This is a graph showing the elemental leaching results of the material and the control material in Example 1 of the present invention during the reaction process; Figure 8 The figure shows the experimental results of quenching of active species in the PMS system activated by the material and the control material in Example 1 of this invention; Figure 9 This is an experimental diagram illustrating the verification of active sites in the material-activated PMS system of Example 1 of the present invention. Figure 10 The image shows the removal effect of the material in Example 1 of this invention on different organic pollutants. Figure 11 The figure shows the experimental results of the cyclic stability of the material in Example 1 of the present invention. Detailed Implementation
[0021] This invention provides a biotite interlayer confined copper catalytic material, comprising a biotite framework and copper species loaded between the layers of the biotite framework, wherein the copper species are electronically coupled to the intrinsic Fe(II) structure in the biotite framework. The copper species include Cu(I) and / or Cu(II); The biotite interlayer confined copper catalytic material contains 0.2-3 wt.% copper and 4-9 wt.% iron.
[0022] In this invention, the copper content in the biotite interlayer confined copper catalyst is preferably 1.07~2.95 wt.%, specifically 1.07 wt.%, 1.44 wt.%, 1.46 wt.%, 2.25 wt.%, 2.28 wt.%, 2.31 wt.%, 2.34 wt.%, 2.41 wt.%, 2.59 wt.%, 2.69 wt.%, 2.77 wt.%, 2.89 wt.%, or 2.95 wt.%, and the iron content is preferably 4.58~8.18 wt.%, specifically 4.58 wt.%, 5.73 wt.%, 6.96 wt.%, 6.97 wt.%, 6.98 wt.%, 7.02 wt.%, 7.15 wt.%, 7.18 wt.%, 7.42 wt.%, 7.51 wt.%, 7.56 wt.%, 7.67 wt.%, 7.83 wt.%, or 8.18 wt.%.
[0023] In this invention, the K content in the biotite interlayer confined catalytic material is lower than the K content in the purified biotite, specifically it can be 1.62 wt.%, 1.86 wt.%, 1.92 wt.%, 2.03 wt.%, 2.04 wt.%, 2.15 wt.%, 2.39 wt.%, 2.77 wt.%, 2.82 wt.%, 2.83 wt.%, 2.86 wt.%, 2.98 wt.%, 3.05 wt.%, or 4.49 wt.%.
[0024] In the X-ray diffraction spectrum of the biotite interlayer confined copper catalytic material described in this invention, the characteristic peak of the 001 crystal plane of purified biotite at 2θ=8.8° is weakened, and a new 001 characteristic peak appears at 2θ=6.0°~6.2°, indicating that the interlayer structure of biotite has changed.
[0025] In this invention, the copper species can form a synergistic active site with the intrinsic iron structure of biotite for activating persulfate.
[0026] This invention also provides a method for preparing the biotite interlayer confined copper catalytic material described in the above technical solution, comprising the following steps: Biotite powder was purified using a buffer solution to obtain purified biotite powder; the pH value of the buffer solution was 4-6. The purified biotite powder and copper salt solution were mixed and the pH of the system was adjusted to 1-5. The mixture was then subjected to ultrasonic treatment in an oxygen-deficient environment to separate the solid and liquid. The resulting solid was washed and dried sequentially to obtain the biotite interlayer confined copper catalytic material.
[0027] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.
[0028] The present invention purifies biotite powder using a buffer solution to obtain purified biotite powder; the pH value of the buffer solution is 4-6.
[0029] In this invention, the biotite powder is preferably obtained by pulverizing and sieving natural biotite in sequence, and the sieving is preferably done with a 200-mesh sieve, taking the undersize portion.
[0030] In this invention, the buffer solution is preferably an acetate-sodium acetate buffer solution with pH=5.
[0031] In this invention, the purification process specifically involves: mixing and stirring biotite powder and a buffer solution, followed by washing and drying sequentially; the stirring time is preferably 24 hours; the washing is preferably done with deionized water, and the number of washes is preferably 3 times; the drying temperature is preferably 60°C, and the drying time is preferably 12 hours. This purification process removes carbonate impurities from the biotite powder mineral.
[0032] After obtaining the purified biotite powder, the present invention mixes the purified biotite powder with a copper salt solution and adjusts the pH value of the system to 1-5, then performs ultrasonic treatment in an oxygen-deficient environment to separate the solid and liquid. The obtained solid is then washed and dried sequentially to obtain the biotite interlayer confined copper catalytic material.
[0033] In this invention, the copper salt in the copper salt solution preferably includes one or more of copper nitrate, copper chloride, and copper sulfate; the concentration of the copper salt solution is preferably 0.05~0.4 mol / L, specifically 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L, or 0.4 mol / L.
[0034] In this invention, the solvent for the copper salt solution preferably includes water and an alcohol solvent, and the alcohol solvent preferably includes one or more of ethanol, isopropanol, and ethylene glycol. The volume fraction of the alcohol solvent in the solvent is preferably 5-40%, specifically 30%. In an embodiment of this invention, the mixing of purified biotite powder and copper salt solution specifically involves adding purified biotite powder to a copper-containing water-alcohol mixture.
[0035] In this invention, the pH value of the system is preferably adjusted to 1-4 before ultrasonic treatment, and more preferably the pH value is adjusted to 3-4. In the embodiments, it is specifically 1, 2 or 4.
[0036] In this invention, nitrogen gas is preferably introduced into the ultrasonic treatment system to reduce dissolved oxygen and provide an oxygen-deficient environment; the nitrogen gas introduction time is preferably 20-30 minutes.
[0037] In this invention, the preferred frequency of the ultrasonic treatment is 20-60 kHz, the preferred power of the probe-type ultrasonic treatment is 300-800 W, specifically 300 W or 500 W, and the preferred ultrasonic treatment time is 30-120 min, specifically 30 min, 60 min, 90 min, or 120 min. The ultrasonic treatment preferably employs a pulsed ultrasonic mode. During the ultrasonic treatment, the system temperature is preferably kept below 40°C, more preferably below 35°C, through ice bath or circulating cooling. In an embodiment of this invention, a pulsed ultrasonic treatment at 20 kHz, 500 W, with a 2-second working / 2-second intermittent pulse mode is used for 90 min, with the system temperature not exceeding 35°C. This invention performs ultrasonic treatment under oxygen-deficient and temperature-controlled conditions, allowing copper species to enter the biotite interlayer along the edges, defects, and microcracks, where K and Cu undergo ion exchange.
[0038] In this invention, after ultrasonic treatment, the system is preferably allowed to stand and cool to room temperature before solid-liquid separation, which is preferably centrifugation. The washing is preferably performed by alternating washing with deionized water and ethanol 3 to 6 times until no copper ions remain in the washing solution. The drying is preferably freeze-drying, and the freeze-drying time is preferably 24 hours.
[0039] The present invention also provides the application of the biotite interlayer confined copper catalyst material described in the above technical solution or the biotite interlayer confined copper catalyst material obtained by the above preparation method in the removal of organic pollutants.
[0040] In this invention, the organic pollutants preferably include one or more of phenols, dyes and antibiotics, and more preferably one or more of 4-chlorophenol, methyl orange, acetaminophen and ciprofloxacin.
[0041] In this invention, the application preferably includes the following steps: mixing the biotite interlayer confined copper catalyst material, the system to be treated containing organic pollutants, and persulfate, and reacting them under stirring and light-protected conditions to achieve the oxidative degradation of organic pollutants.
[0042] In this invention, the mass ratio of the biotite interlayer confined copper catalyst to the volume of the system to be treated is preferably 0.5 g: 1 L, and the concentration of organic pollutants in the system to be treated is preferably 10 mg / L.
[0043] In this invention, the molar ratio of permonosulfate (PMS) to the volume of the system to be treated is preferably 0.5 mmol:1 L. The biotite interlayer confined copper catalyst of this invention can activate permonosulfate.
[0044] In this invention, the mixture of the biotite interlayer confined copper catalyst, the system to be treated containing organic pollutants, and persulfate preferably further includes: adjusting the initial pH of the resulting mixture to 5.6.
[0045] In this invention, the stirring speed is preferably 400 rpm; the reaction time is preferably 10 min; and the catalytic material of this invention can achieve rapid degradation of pollutants.
[0046] In an application example of the present invention, the biotite interlayer confined copper catalyst material is added at a concentration of 0.5 g / L to a 10 mg / L solution of 4-chlorophenol, methyl orange, acetaminophen, or ciprofloxacin, and reacted under the conditions of 0.5 mM PMS concentration, initial pH value of 5.6, stirring speed of 400 rpm, and protection from light.
[0047] This invention uses natural biotite as a framework carrier. Through anoxic pulsed ultrasonic treatment in a copper-containing water-alcohol mixture, copper species are introduced into the interlayer along the edges, defects, and microcracks of the biotite layers, forming confined copper active sites. Simultaneously, relying on the electronic coupling between the intrinsic Fe(II) structure of biotite and the interlayer copper species, a catalytic system with high persulfate activation capacity is constructed, thereby achieving efficient removal of organic pollutants. This invention develops a biotite interlayer confined copper-based active material that leverages the synergistic effect of the intrinsic Fe(II) structure of biotite and the interlayer copper sites, possesses well-defined structural characteristics, is simple to prepare, and exhibits excellent catalytic performance, demonstrating significant technical value and practical significance.
[0048] To further illustrate the present invention, the following detailed description, in conjunction with the accompanying drawings and embodiments, describes the biotite interlayer confined copper catalytic material, its preparation method, and its applications, but these descriptions should not be construed as limiting the scope of protection of the present invention.
[0049] Example 1 (1) Take 50.0 g of natural biotite powder pre-milled to 200 mesh, add acetic acid-sodium acetate buffer solution with pH=5 and stir for 24 h, then wash with deionized water 3 times, and then dry at 60℃ for 12 h to obtain purified biotite powder. (2) Weigh 5.0 g of the purified biotite powder and mix it with 200 mL of 0.15 M Cu(NO3)2 water / ethanol mixed solution (water:ethanol volume ratio 70:30). Adjust the pH of the solution to 4.0 with dilute nitric acid, purge with nitrogen for 30 min to remove oxygen, and treat with 20 kHz probe pulse ultrasound for 90 min under ice bath temperature control. The ultrasound power is 500 W, the pulse mode is 2 s working and 2 s intermittent. The system temperature does not exceed 35℃ during the reaction. (3) After the ultrasound, the solid and liquid were separated by centrifugation, and the mixture was washed three times with deionized water and ethanol until there were no obvious copper ions left in the washing solution. Then it was freeze-dried for 24 h to obtain the biotite interlayer confined copper-based active material (biotite interlayer confined copper catalytic material).
[0050] The total Fe and Cu content in the obtained material was determined by atomic absorption spectrophotometry. The Fe content was 7.18 wt.% and the Cu content was 2.69 wt.%.
[0051] Application Example 1 The biotite interlayer confined copper-based active material described in Example 1 was added to a 4-chlorophenol solution with an initial concentration of 10 mg / L at a dosage of 0.5 g / L. PMS was added to make the initial concentration 0.5 mM, the initial pH of the system was controlled at 5.6, the stirring speed was 400 rpm, and the reaction was carried out for 10 min under light-protected conditions.
[0052] Tests showed that the removal rate of 4-chlorophenol was 100% after 10 minutes of reaction.
[0053] In the following examples or comparative examples, the pollutant removal rate test method is the same as in Application Example 1.
[0054] Comparative Example 1 The difference from Example 1 is that only step (1) is performed to obtain purified biotite powder (i.e., without copper salt ultrasonic intercalation).
[0055] The purified biotite powder material had an Fe content of 9.29 wt.% and a Cu content of 0 wt.%.
[0056] The removal rate of 4-chlorophenol was 72% according to the test.
[0057] Comparative Example 2 The difference from Example 1 is that in step (2), a water / ethanol mixed solvent (water:ethanol volume ratio 70:30) is used instead of Cu(NO3)2 water / ethanol mixed solution, and the remaining steps are the same as in Example 1.
[0058] The obtained material has an Fe content of 8.31 wt.% and a Cu content of 0 wt.%.
[0059] The removal rate of 4-chlorophenol was 57% according to the test.
[0060] Comparative Example 3 The difference from Example 1 is that ultrasound is not applied in step (2), and magnetic stirring is performed for 90 min under the same solution, pH value, nitrogen atmosphere and temperature control conditions. The remaining steps are the same as in Example 1.
[0061] The obtained material has an Fe content of 8.92 wt.% and a Cu content of 0.84 wt.%.
[0062] The removal rate of 4-chlorophenol was 77.6% as tested.
[0063] Example 2 The difference from Example 1 is that the pulse ultrasound treatment time in step (2) is 30 min, and the rest of the steps are the same as in Example 1.
[0064] The obtained material has an Fe content of 8.18 wt.% and a Cu content of 2.41 wt.%.
[0065] The removal rate of 4-chlorophenol was 91.2% as tested.
[0066] Example 3 The difference from Example 1 is that the pulse ultrasound treatment time in step (2) is 60 min, and the rest of the steps are the same as in Example 1.
[0067] The obtained material has an Fe content of 7.51 wt.% and a Cu content of 2.59 wt.%.
[0068] Tests showed that the removal rate of 4-chlorophenol was 95%.
[0069] Example 4 The difference from Example 1 is that the pulse ultrasound treatment time in step (2) is 120 min, and the rest of the steps are the same as in Example 1.
[0070] The obtained material has an Fe content of 6.96 wt.% and a Cu content of 2.77 wt.%.
[0071] The removal rate of 4-chlorophenol was 100% as tested.
[0072] Example 5 The difference from Example 1 is that CuCl2 with an equimolar concentration is used instead of Cu(NO3)2 in step (2), while the rest of the steps are the same as in Example 1.
[0073] The obtained material has an Fe content of 7.42 wt.% and a Cu content of 2.31 wt.%.
[0074] The removal rate of 4-chlorophenol was tested to be 87.7%.
[0075] Example 6 The difference from Example 1 is that CuSO4 with an equimolar concentration is used instead of Cu(NO3)2 in step (2), while the rest of the steps are the same as in Example 1.
[0076] The obtained material has an Fe content of 7.56 wt.% and a Cu content of 2.25 wt.%.
[0077] The removal rate of 4-chlorophenol was 76.2% as tested.
[0078] Example 7 The difference from Example 1 is that the concentration of Cu(NO3)2 solution in step (2) is 0.1 M, and the rest of the steps are the same as in Example 1.
[0079] The obtained material has an Fe content of 7.67 wt.% and a Cu content of 2.34 wt.%.
[0080] The removal rate of 4-chlorophenol was 93.7% as tested.
[0081] Example 8 The difference from Example 1 is that the concentration of Cu(NO3)2 solution in step (2) is 0.2 M, and the rest of the steps are the same as in Example 1.
[0082] The obtained material has an Fe content of 7.15 wt.% and a Cu content of 2.77 wt.%.
[0083] The removal rate of 4-chlorophenol was 100% as tested.
[0084] Example 9 The difference from Example 1 is that the concentration of Cu(NO3)2 solution in step (2) is 0.3 M, and the rest of the steps are the same as in Example 1.
[0085] The obtained material has an Fe content of 7.02 wt.% and a Cu content of 2.89 wt.%.
[0086] The removal rate of 4-chlorophenol was 100% as tested.
[0087] Example 10 The difference from Example 1 is that the concentration of Cu(NO3)2 solution in step (2) is 0.4 M, and the rest of the steps are the same as in Example 1.
[0088] The obtained material has an Fe content of 6.97 wt.% and a Cu content of 2.95 wt.%.
[0089] The removal rate of 4-chlorophenol was 100% as tested.
[0090] Example 11 The difference from Example 1 is that the pH value of the reaction solution is adjusted to 2.0 in step (2), while the rest of the steps are the same as in Example 1.
[0091] The obtained material has an Fe content of 5.73 wt.% and a Cu content of 2.28 wt.%.
[0092] The removal rate of 4-chlorophenol was 85.4% as tested.
[0093] Example 12 The difference from Example 1 is that the pH value of the reaction solution is adjusted to 1.0 in step (2), while the rest of the steps are the same as in Example 1.
[0094] The obtained material has an Fe content of 4.58 wt.% and a Cu content of 1.07 wt.%.
[0095] The removal rate of 4-chlorophenol was 68.5% as tested.
[0096] Example 13 The difference from Example 1 is that the probe ultrasonic power in step (2) is 300 W, and the rest of the steps are the same as in Example 1.
[0097] The obtained material has an Fe content of 7.83 wt.% and a Cu content of 1.46 wt.%.
[0098] The removal rate of 4-chlorophenol was 81.2% as tested.
[0099] Example 14 The difference from Example 1 is that in step (2), deionized water is used instead of water / ethanol mixed solvent, the Cu(NO3)2 concentration is the same, and the rest of the steps are the same as in Example 1.
[0100] The obtained material has an Fe content of 6.98 wt.% and a Cu content of 1.44 wt.%.
[0101] The removal rate of 4-chlorophenol was tested to be 86.3%.
[0102] Example 15 The difference from Example 1 is that pure ethanol is used instead of water / ethanol mixed solvent in step (2), the concentration of Cu(NO3)2 is the same, and the rest of the steps are the same as in Example 1.
[0103] The obtained material has an Fe content of 9.12 wt.% and a Cu content of 0.21 wt.%.
[0104] The removal rate of 4-chlorophenol was 74% as tested.
[0105] Application Example 2 The difference from Application Example 1 is that PMS is not added, but the rest of the steps are the same.
[0106] The removal rate of 4-chlorophenol was 5% as tested.
[0107] Application Example 3 The difference from Application Example 1 is that no biotite material is added; only PMS is added for the reaction.
[0108] The removal rate of 4-chlorophenol was 11% according to the test results.
[0109] Application Example 4 The difference from Application Example 1 is that 100 mM methanol is added to the reaction system (before stirring) as a quencher.
[0110] The removal rate of 4-chlorophenol was 48.3% as tested.
[0111] Application Example 5 The difference from Application Example 1 is that 100 mM tert-butanol is added to the reaction system as a quencher.
[0112] The removal rate of 4-chlorophenol was 60.1% as tested.
[0113] Application Example 6 The difference from Application Example 1 is that 100 mM furfuryl alcohol is added to the reaction system as a quencher.
[0114] The removal rate of 4-chlorophenol was 2.9% as tested.
[0115] Application Example 7 The difference from Application Example 1 is that the material obtained in Comparative Example 1 is used as the reaction material, and 100 mM methanol is added to the reaction system as a quencher.
[0116] The removal rate of 4-chlorophenol was 6.5% as tested.
[0117] Application Example 8 The difference from Application Example 1 is that the material obtained in Comparative Example 1 is used as the reaction material, and 100 mM tert-butanol is added to the reaction system as a quencher.
[0118] The removal rate of 4-chlorophenol was 25.9% as tested.
[0119] Application Example 9 The difference from Application Example 1 is that the material obtained in Comparative Example 1 is used as the reaction material, and 100 mM furfuryl alcohol is added to the reaction system as a quencher.
[0120] The removal rate of 4-chlorophenol was 2.8% as tested.
[0121] Application Example 10 The difference from Application Example 1 is that the material obtained in Comparative Example 3 is used as the reaction material, and 100 mM methanol is added to the reaction system as a quencher.
[0122] The removal rate of 4-chlorophenol was 3.5% as tested.
[0123] Application Example 11 The difference from Application Example 1 is that the material obtained in Comparative Example 3 is used as the reaction material, and 100 mM tert-butanol is added to the reaction system as a quencher.
[0124] The removal rate of 4-chlorophenol was 30.7% as tested.
[0125] Application Example 12 The difference from Application Example 1 is that the material obtained in Comparative Example 3 is used as the reaction material, and 100 mM furfuryl alcohol is added to the reaction system as a quencher.
[0126] The removal rate of 4-chlorophenol was 2.3% as tested.
[0127] Application Example 13 The difference from Application Example 1 is that 1 mM of new copper reagent, namely 2,9-dimethyl-1,10-phenanthroline, is added to the reaction system as a copper site masking agent.
[0128] The removal rate of 4-chlorophenol was 23.2% as tested.
[0129] Application Example 14 The difference from Application Example 1 is that 1 mM phenanthroxazine is added to the reaction system as an iron site masking agent.
[0130] The removal rate of 4-chlorophenol was 77.6% as tested.
[0131] Application Example 15 The difference from Application Example 1 is that methyl orange is used instead of 4-chlorophenol as the target pollutant.
[0132] Tests showed that the removal rate of methyl orange was 100%.
[0133] Application Example 16 The difference from Application Example 1 is that acetaminophen is used instead of 4-chlorophenol as the target pollutant.
[0134] The test showed that the removal rate of acetaminophen was 92%.
[0135] Application Example 17 The difference from Application Example 1 is that ciprofloxacin is used instead of 4-chlorophenol as the target pollutant.
[0136] Tests showed that the removal rate of ciprofloxacin was 90%.
[0137] Application Example 18 Using the biotite interlayer confined copper-based active material obtained in Example 1 as a catalyst, a cyclic experiment was conducted under the same reaction conditions as in Application Example 1. After each reaction, 4-chlorophenol was added to the system to a concentration of 10 mg / L, and the reaction was repeated. After 5 cycles, the removal rate of 4-chlorophenol was 89%.
[0138] To verify the structural characteristics, elemental composition, valence state changes, catalytic performance, and reaction mechanism of the biotite interlayer confined copper catalytic material prepared in this invention, the material obtained in Example 1 and other materials were systematically characterized and their performance tested. The results are listed in Table 1 and... Figures 1-11 The analysis of elemental composition, crystal structure, bond structure, and elemental valence states verified whether copper species had been successfully introduced into the biotite interlayer and interacted with the structural iron in biotite. The results of PMS activation degradation kinetics, elemental leaching, free radical quenching, and active site verification (adding free radical quenchers such as methanol, tert-butanol, and furfuryl alcohol to the reaction system to investigate the effects of different active species on the pollutant degradation process and verify the reaction mechanism of the material in the PMS activation system; simultaneously, adding new copper reagent and phenanthrone as active site masking agents to the reaction system to verify the role of interlayer copper sites and structural iron sites in the PMS activation process) further demonstrated the PMS activation ability and structural Fe-Cu synergistic effect of the material of this invention. The results of different pollutant removal and cycling experiments further illustrated the universality and cycling stability of the material of this invention.
[0139] Table 1. Elemental composition analysis of materials and control materials in Example 1.
[0140] Note: The Fe and Cu contents in the obtained materials were measured by atomic absorption spectrophotometry of the wet digestion samples.
[0141] Compared to Comparative Example 3 without ultrasound, the sample in Example 1 showed a higher Cu content accompanied by a decrease in K content, indicating that pulsed ultrasound and a water-alcohol wetting environment can promote the entry of copper species into the biotite interlayer or interlayer edge sites. Furthermore, comparing the changes in Fe, Cu, and K content in Examples 1 and Examples 14-15, it was found that neither pure water nor pure ethanol effectively promoted copper intercalation and the protection of structural iron. Further comparison of Examples 2, 3, and 4 showed that with increasing ultrasound time, the Cu content loaded in biotite initially increased and then leveled off. The overall increase in Cu content was consistent with the decreasing trend in K content, indicating that Cu is more likely to enter the biotite interlayer under ultrasound-assisted conditions.
[0142] Depend on Figure 1It can be seen that purified biotite exhibits a characteristic diffraction peak of the 001 crystal plane at 2θ = 8.8°, corresponding to an interlayer spacing of approximately 1.0 nm. The characteristic peak of the material obtained in Example 1 is weakened, and a new 001 characteristic peak appears at 2θ = 6.0°~6.2°. This indicates that ultrasonic treatment with the copper-containing water-alcohol mixture alters the interlayer structure of biotite. Comparative Examples 2 and 3 demonstrate that a solvent / acidic environment alone or without ultrasonic conditions cannot significantly alter the interlayer characteristics of biotite. Figure 2 The subtle shifts in the interlayer hydroxyl water and Si-O-Si stretching vibrations in the mid-infrared spectrum can be further used to demonstrate the transformation of interlayer species. For example... Figure 3 As shown, the fitting results of the high-resolution Cu 2p spectrum indicate that Cu(I) / (II) mixed valence states coexist. This suggests that during ultrasonic intercalation, Cu(II) not only enters the interlayer but also forms a more active cuprous species due to the interlayer confinement environment and the electron-donating effect of Fe(II) structure. Meanwhile, the Fe 2p spectrum ( Figure 4 The decrease in the Fe(II) ratio in Example 1 indicates that partial oxidation of the biotite-structured iron occurred during the copper introduction process. These results collectively demonstrate that copper can be deposited in the biotite interlayer and can electronically couple with the biotite-structured iron, providing a valence state basis for subsequent PMS activation.
[0143] like Figure 5 As shown, under the same reaction conditions, the material obtained in Example 1 exhibited the highest removal efficiency for 4-chlorophenol. After 10 min of reaction, the removal rate of 4-chlorophenol reached 100%. Comparison of Application Examples 2 and 3 revealed that neither the absence of PMS nor the addition of PMS alone could effectively remove 4-chlorophenol, indicating that neither adsorption nor reduction was effective in removing it. In contrast, the 10-min removal rates of 4-chlorophenol for Comparative Examples 1, 2, 3, 2, 3, and 4 were 72%, 57%, 77.6%, 91.2%, 95%, and 100%, respectively, indicating that the main reactive sites of biotite changed from structural iron to confined intercalated copper sites.
[0144] like Figure 6 As shown in Examples 5 to 15, it is further demonstrated that the type of copper salt, copper salt concentration, pH value of the reaction solution, ultrasonic power, and solvent composition all affect the performance of the material in activating PMS, with the sample obtained under the conditions corresponding to Example 1 representing the optimal conditions. Figure 7As shown, during the PMS activation of 4-chlorophenol, the leaching concentrations of Fe and Cu ions in the sample of Example 1 were 1.2 mg / L and 0.1 mg / L, respectively, less than 0.5% of the material's concentration. Compared to Example 1, the leaching concentration of Fe in Comparative Example 1 was 3.41 mg / L, and the leaching concentrations of Fe and Cu ions in Comparative Example 3 were 2.86 mg / L and 1.25 mg / L, respectively. This indicates that the interlayer confined copper coordination environment is more stable and less prone to secondary pollution. This also demonstrates that the active copper sites and structural iron sites in the material of Example 1 of this invention have good structural stability, and the reaction process is mainly dominated by the solid-phase catalytic material, rather than a simple homogeneous dissolution reaction.
[0145] like Figure 8 As shown, in the system of Example 1, the removal rate of 4-chlorophenol decreased from 100% to 48% after adding 100 mM methanol; the removal rate decreased to 60% after adding 100 mM tert-butanol; and the removal rate decreased to 3% after adding 100 mM furfuryl alcohol. This indicates that the active species in the system of Example 1 is... 1 O2 is the main component, SO4 - · and ·OH are secondary inhibitors. In contrast, in Comparative Example 1 and Comparative Example 3 systems, after adding the same quencher, methanol and tert-butanol played the main inhibitory roles. This indicates that the material of the present invention, compared with the control system, significantly transforms the reactive oxygen species generation pathway into · OH. 1 ROS generation path based on O2.
[0146] like Figure 9 As shown, after adding 1 mM of new copper reagent to the system of Example 1, the removal rate of 4-chlorophenol decreased from 100% to 23.2%; after adding 1 mM phenanthroline, the removal rate of 4-chlorophenol decreased to 77.6%. These results indicate that the masking of both copper and iron sites significantly inhibits the reaction, suggesting that both interlayer copper sites and biotite structural iron sites participate in the PMS activation process. The inhibitory effect of the new copper reagent is more pronounced, indicating that copper sites contribute more significantly to this system; furthermore, the significant inhibitory effects of both reagents further demonstrate the existence of structural Fe-Cu synergistic active centers in the material of this invention.
[0147] like Figure 10 As shown, under the same reaction conditions as in Example 1, the material of the present invention exhibits good removal effects on various pollutants. Specifically, after 10 min of reaction, the removal rates of methyl orange, acetaminophen, and ciprofloxacin reached 100%, 92%, and 90%, respectively. This indicates that the material of the present invention is not only suitable for phenolic pollutants but also has good removal capabilities for dyes and antibiotics, demonstrating its good versatility.
[0148] like Figure 11As shown, after five consecutive cycles, the removal rate of 4-chlorophenol by the material of this invention remains at approximately 90%. This indicates that the catalytic performance of the material of this invention exhibits minimal degradation during recycling, demonstrating good structural stability and reusability.
[0149] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A biotite interlayer confined copper catalytic material, characterized in that, It includes a biotite framework and copper species loaded between the layers of the biotite framework, wherein the copper species are electronically coupled to the intrinsic Fe(II) structure in the biotite framework. The copper species include Cu(I) and / or Cu(II); The biotite interlayer confined copper catalytic material contains 0.2-3 wt.% copper and 4-9 wt.% iron.
2. The biotite interlayer confined copper catalytic material according to claim 1, characterized in that, The biotite interlayer confined copper catalyst has a copper content of 1.07~2.95 wt.% and an iron content of 4.58~8.18 wt.%.
3. The method for preparing the biotite interlayer confined copper catalytic material according to claim 1 or 2, characterized in that, Includes the following steps: Biotite powder was purified using a buffer solution to obtain purified biotite powder; the pH value of the buffer solution was 4-6. The purified biotite powder and copper salt solution were mixed and the pH of the system was adjusted to 1-5. The mixture was then subjected to ultrasonic treatment in an oxygen-deficient environment to separate the solid and liquid. The resulting solid was washed and dried sequentially to obtain the biotite interlayer confined copper catalytic material.
4. The preparation method according to claim 3, characterized in that, The copper salt in the copper salt solution includes one or more of copper nitrate, copper chloride, and copper sulfate; the concentration of the copper salt solution is 0.05~0.4 mol / L.
5. The preparation method according to claim 3 or 4, characterized in that, The solvent of the copper salt solution includes water and an alcohol solvent, wherein the alcohol solvent includes one or more of ethanol, isopropanol and ethylene glycol, and the volume fraction of the alcohol solvent in the solvent is 5-40%.
6. The preparation method according to claim 3, characterized in that, The pH of the system was adjusted to 3-4 after the purified biotite powder and copper salt solution were mixed.
7. The preparation method according to claim 3, characterized in that, The frequency of the ultrasonic treatment is 20~60kHz, and the ultrasonic power is 300~800W.
8. The preparation method according to claim 3 or 7, characterized in that, The ultrasonic treatment time is 30~120 minutes.
9. The application of the biotite interlayer confined copper catalyst material according to claim 1 or 2, or the biotite interlayer confined copper catalyst material obtained by the preparation method according to any one of claims 3 to 8, in the removal of organic pollutants.
10. The application according to claim 9, characterized in that, The application includes the following steps: mixing the biotite interlayer confined copper catalyst, the system to be treated containing organic pollutants, and persulfate, and reacting them under stirring and light-protected conditions.